Variations in soil physical properties, distribution and storage of micronutrients in soil as influenced by high density mango (Mangifera indica L.) plantations - ADAK, TARUN; KUMAR, KAILASH; SINGH, VINOD KUMAR (Journal of Soil and Water Conservation, 2020)
The aim of this study was to assess the vertical distribution and storage of micronutrients (Fe, Mn, Cu and Zn) and their relationship with soil properties as influenced by high density mango plantation systems maintained over 20 years under semiarid subtropical condition. The study indicated that planting density had strong impact on the micronutrient distribution and its storage in soil. The micronutrient concentrations under different density systems had higher content in the top layer with a tendency to decrease down the depths. Micronutrients densities were estimated using the values of micronutrient concentrations, bulk densities and depth of soil layer. Micronutrients densities were significantly higher in high density systems as compared to normal density plantation. Maximum distribution of Zn, Cu, Mn and Fe densities was recorded in the category 1.1 to 1.5 kg ha-1 (54.2%), 11 to 20 kg ha-1 (62.5%), 31 to 40 kg ha-1 (66.7%) and 21 to 30 kg ha-1(45.8%) respectively. Significant positive correlation was observed between soil organic carbon (SOC) and micronutrients (r = 0.725** to 0.878**) while inverse relationship was recorded between available Zn, Fe and Cu densities with clay + silt content (r = -0.62* to -0.92**). SOC content had positive correlation with clay content (r = 0.951**) and inverse relation with clay + silt content (r = -0.982**). Clay and clay + silt should be considered as an important soil factor as they might impact the micronutrient stocks and SOC content.